TO THE QUESTION OF THE RELATIONSHIP OF TEACHERS’ COMMITMENT TO INNOVATIONS AND SOCIOPSYCHOLOGICAL CLIMATE IN UNIVERSITIES - I. B. Avakyan (Образование и наука)
Introduction. In the modern system of higher professional education, high standards are imposed on the quality of educational activity provided the relevance of the problem of the teacher’s commitment to innovation, which is expected to be implemented in the conditions of a favourable socio-psychological climate. The aim of the publication is to present the research results on identification of the dependence level of the teachers’ commitment to innovations and sociopsychological climate of teaching staff in higher educational institutions. Methodology and research methods. Various empirical methods were used in the course of the research: testing, questioning, polling, observation, conversation. The following techniques were involved as psychodiagnostic tools: the method “Assessment of Psychological Climate of Teaching Staff” by A. N. Lutoshkin; the rapid assessment methodology on studying social and psychological climate by Yu. A. Shalyto and O. S. Mikhalyuk; J. Ceserani’s questionnaire “Workplace Innovation Quotient”; the questionnaire of personnel’s commitment to innovations developed by V. V. Panteleeva and T. P. Knysheva. Processing of the data obtained was conducted by means of mathematical statics methods: the One-Sample Kolmogorov-Smirnov Test, the Spearman’s Rank Correlation Coefficient, and the Method of Linear Regression. Results and scientific novelty. The content of the concept of “commitment to innovations of a university teacher” is disclosed; the concept of “socio-psychological climate” is concretized. The conducted research, with the sample consisted of 2036 teachers on the basis of 9 higher educational institutions of Russia, made it possible to identify the presence of a favourable socio-psychological climate in the teaching staff of all the universities. The correlation of the level of innovation factor with the indicators of a personality creative potential and psychological commitment to innovations of the research participants, at emotional, motivational, cognitive, personal (instrumental), organizational levels, has shown the linear dependence of this commitment on socio-psychological climate: the better the level is, the more the teachers commit themselves to innovations and encourage themselves to successful innovation implementation in the educational process. Practical significance. The research materials can be used by the managers and representatives of the teaching staff to implement the programs of innovative reorganization.